Chemical Composition and Biological Activity of Essential Oils from Different Species of Piper from Panama - Santana, Ana I.; Vila, Roser; Cañigueral, Salvador; Gupta, Mahabir P. (Planta Medica, 2016)
The chemical composition of leaf essential oils from 11 species of Piper from Panama was analyzed by a combination GC-FID and GC-MS procedures. Six of them had sesquiterpene hydrocarbons as major constituents, three were characterized by monoterpene hydrocarbons, one by a diterpene, and one by a phenylpropanoid, dillapiole. The main components identified in each species were: cembratrienol (25.4 %) in Piper augustum; β-pinene (26.6 %) in Piper corrugatum; α-pinene (19.4 %) in Piper curtispicum; trans-β-farnesene (63.7 %) in Piper darienense; p-cymene (43.9 %) in Piper grande; dillapiole (57.7 %) in Piper hispidum; linalool (14.5 %), α-phellandrene (13.8 %), and limonene (12.2 %) in Piper jacquemontianum; β-caryophyllene (45.2 %) in Piper longispicum; linalool (16.5 %), α-phellandrene (11.8 %), limonene (11.4 %), and p-cymene (9.0 %) in Piper multiplinervium; β-selinene (19.0 %), β-elemene (16.1 %), and α-selinene (15.5 %) in Piper reticulatum; and germacrene D (19.7 %) in Piper trigonum. The essential oils of P. hispidum and P. longispicum at a concentration of 250 µg/mL showed larvicidal activity against Aedes aegypti, while the oils from P. curtispicum, P. multiplinervium, P. reticulatum, and P. trigonum were inactive (LC100 ≥ 500 µg/mL). The essential oils of P. grande, P. jacquemontianum, and P. multiplinervium showed no significant antifungal activity (MIC > 250 µg/mL) against several yeasts and filamentous fungal strains.
Keywords: Piper; Piperaceae; essential oil; cembratrienol; larvicidal; Panama